A Phage Therapy Guide for Clinicians and Basic Scientists: Background and Highlighting Applications for Developing Countries - Khalid, Ali; Lin, Ruby C. Y.; Iredell, Jonathan R. (Frontiers in Microbiology, 2021)
Approximately 10% of global health research is devoted to 90% of global disease burden (the so-called ‘10/90 Gap’) and it often neglects those diseases most prevalent in low-income countries. Antibiotic resistant bacterial infections are known to impact on healthcare, food security and socio-economic fabric in the developing countries. With a global antibiotic resistance crisis currently reaching a critical level, the unmet needs in the developing countries are even more striking. The failure of traditional antimicrobials has led to renewed interest in the century-old bacteriophage (phage) therapy in response to the urgent need to develop alternative therapies to treat infections. Phage therapy may have particular value in developing countries where relevant phages can be sourced and processed locally and efficiently, breaking specifically the economic barrier of access to expensive medicine. Hence this makes phage therapy an attractive and feasible option. In this review, we draw our respective clinical experience as well as phage therapy research and clinical trial, and discuss the ways in which phage therapy might reduce the burden of some of the most important bacterial infections in developing countries.